Global Secular Trend of Gonadal Size in Men: Review and Analysis of Publications - A. Yu. Seroukhov; A. A. Afoko; I. E. Mamaev (Вестник урологии, 2020)
Introduction. Notwithstanding the general increase in world population, there is a steady decline in birth rate. Studies have shown a tendency towards worsening of qualitative and quantitative indices of the ejaculate. From the foregoing we may also presume a decline in size of male gonads. Nevertheless, information about the tendency of change in testicular size in the population is currently unavailable.Purpose of the study. Assessment of global secular trend as regards changes in the size of testes in men.Materials and methods. A search was conducted on published scientific research in the English language and Russian language in Pubmed and eLibrary. Additional searches in citations of identifiable investigations. A selection of data from publications with metric characteristics of gonads in relatively healthy men aged 18‒60 years. The mean of values obtained were determined and homogenized with the aid of formulae for volume calculations. Statistical analysis of the data was carried out with the aid of the program STATISTICA for Windows v.10.Results. The search yielded 126 identified publications, published between 1902 and 2018. Analysis of the various works led to a selection of 33, which contained information that satisfied the inclusion criteria. Analysis of the obtained data did not reveal any trends in change of testicular size over the past century. Mean arithmetic weighted value was 17,43±5,64; 95% CI (17,32; 17,54).Conclusion. In the light of global trends towards a reduction in fertility, it is necessary to conduct a wide range of varied investigations in order to understand the nature of this process. Standardization of methods of assessment results obtained will help in reducing errors whilst assisting in the analysis of existing tendencies.